Determinación de las principales plagas y enfermedades en los cultivos de plátano barraganete de exportación (Musa paradisiaca L.) en el Sitio Pueblo Arrecho, Cantón El Carmen, Manabi año 2019 - Parrales Cuadros, Luis Ángel (2019)
SUMMARY The present investigation was carried out in the Pueblo Arrecho Site, San Pedro de Suma parish, Canton El Carmen, province of Manabí Year 2019. At 250 meters above sea level, in order to know and determine the main pests and diseases that most affect banana cultivation Barraganete export. The primary information was taken by interviewing the banana producers, who plant more than 45 years. They preferentially cultivate the variety of banana plantations because they have a demand in the international market. The cultural and chemical management to prevent and control pests and diseases is done: black weevil, black and yellow sigatoka, nematodes. The attacks of these pests and diseases were verified in the field, the phenology and time of the crop where the damage is more severe, is not monitored or a written record is kept of the presence or the degree of affectation of the main pests and diseases, in the locality. Key words: Plague, disease, insecticide, application, plantain ban